2017
DOI: 10.4172/2376-0281.1000278
|View full text |Cite
|
Sign up to set email alerts
|

Robots as New Tools in Therapy and Education for Children with Autism

Abstract: Robots are increasingly considered as a promising tool in therapeutic and educational interventions for children with autism spectrum disorder (ASD). International literature indicates that robots can potentially be applied to a wide range of objectives. The aim of this article is to present an overview of robots that are currently used in therapy and educational for children with ASD and to indicate what objectives they address. Focus group sessions (N=9) with ASD professionals (N=53) from nine organisations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…We suppose that robots would be more likely to "catalyze" prosocial behaviors if they interacted directly with the child, without any remote control, and if they endorsed a social role: that of prompter, teacher, helper in critical situations, etc. (Zubrycki and Granosik, 2016;Huijnen et al, 2017). Children with ASD would be therefore efficiently trained to produce and interpret social cues exchanged with the robot, and perhaps could generalize this learning to interpersonal interaction.…”
Section: Social Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…We suppose that robots would be more likely to "catalyze" prosocial behaviors if they interacted directly with the child, without any remote control, and if they endorsed a social role: that of prompter, teacher, helper in critical situations, etc. (Zubrycki and Granosik, 2016;Huijnen et al, 2017). Children with ASD would be therefore efficiently trained to produce and interpret social cues exchanged with the robot, and perhaps could generalize this learning to interpersonal interaction.…”
Section: Social Mediatormentioning
confidence: 99%
“…The key idea of ABA is to increase the probability of desirable behaviors by providing reinforcers in the form of rewards (Skinner, 1981 ). For the purpose of the present study, we chose the two general social skills that are most often targeted by educational interventions in ASD: requesting and turn-taking (Still et al, 2014 ; Huijnen et al, 2017 ). Requesting allows children to initiate a social interaction, express their needs and seek help, and leads to greater independence.…”
Section: Introductionmentioning
confidence: 99%
“…While some of the existing robots could meet many of the therapy objectives, they are still not adequate enough to be used with some of the children on the spectrum who may exhibit hyperactivity and aggression [53]. The majority of the social robots used in the literature are just prototypes, not commercially available, and have yet to find their ways into therapy sessions or special needs schools [52]. Hence, the exposure to such technology is still very limited worldwide and the need to identify potential safety issues arises.…”
Section: Robots and Potential Risksmentioning
confidence: 99%
“…Previous studies have shown that children on the spectrum have strong interest in technology, such as computer applications [48], virtual environments [87], and robots [16,98]. There has been a growing interest in the clinical use of robots to assist in the therapy of children with ASD [10,28,52]. The usage of technology, especially robotics, for ASD therapy opens many possibilities in the early intervention for children with ASD, and toward more personalized therapy [90,91].…”
Section: Introductionmentioning
confidence: 99%
“…Toutefois, pour bénéficier pleinement des avantages souhaités, les enseignants doivent être impliqués dans le choix des scénarios et bénéficier de formation pour conduire adéquatement l'innovation pédagogique (Macknight et Davies, 2013 ;Liu, Salisbury, Vahabzadeh et Sahin, 2017 ;Martín-Gutiérrez, Mora, Añorbe-Díaz et González-Marrero, 2017). L'utilisation des robots à l'école ou à la maison suscite des problèmes de financement ; cela limite l'implication des parties prenantes, ainsi que la concrétisation des résultats préliminaires déjà enregistrés (Huijnen et Lexis et de Witte, 2017 ;Karsenti, Bugmann et Frenette, 2017). Par ailleurs, le recours aux technologies adaptées varie en fonction des milieux éducatifs et selon les systèmes éducatifs concernés (Macknight et Davies, 2013).…”
Section: Défis Des Adaptations Aux Pratiques D'éducationunclassified